Problematika Penerapan Sistem Nazhariyyah Al Wahdah pada Pembelajaran Bahasa Arab di Madrasah Aliyah Se-Kota Metro Tahun 2018 - Novita Rahmi (Institut Agama Islam Negeri (IAIN) Metro, 2019)
This study aims to determine the problems and solutions to the application of the Nazhariyah Al Wahdah system in learning Arabic in the Aliyah Madrasah in Metro City in 2018. This research is a qualitative case study conducted in 3 Aliyah Madrasas in Metro City: MAN 1, MA Muhammadiyah, and MA Raudhatut Thalibin. The researcher uses interactive model data analysis. Based on data collection techniques: In-depth interviews, documentation, and participatory observation, the researchers concluded that these problems occur due to inadequate time allocation and unavailability of language laboratories. And professional teachers in the field of Arabic and the existence of a language environment are the solution to this problem.